(untitled) (Experimental biology, 2016)
This paper presents data phenotypic screening of M5 mutant lines of spring wheat; devel-oped on the genetic basis of Zhenis cultivar and the use of different doses of gamma radiation; 100 and 200 Gy; on the parameter of grain area. New sources in both types of mutant germplasm were identified for genetic improvement of quantitative trait; grain area. All mutant lines of both types of wheat germplasm had significantly higher values of the parameter in comparison with the cultivar Zhenis that correspond to differences in the interval 18.85% -31.95%.Dose of 200 Gy more positive induces phenotypic changes in the parameter of grain area compared with a dose of 100 Gy and it is a more effective tool for genetic variability.